Justice and cities : metro morals - Davidson, Mark, 1979- (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book explores different theories of justice and explains how these connect to broader geographical questions and inform our understanding of urban problems. Part 1 explores and assesses theories of justice including Utilitarianism, Libertarianism, Liberalism, Marxism, Communitarianism, Conservativism, considering how these theories shape our view of the concept of a city. An emphasis on disconnection, particularly, and discontinuities now pushes us to think about urbanization (as a process) and cities (as objects in the landscape) in new ways. Recent urban theory debates raise questions around the issue of urban justice: do we draw on abstract, universally applicable moral theories to assess cities, or shift to culturally-embedded moral judgement? In Part 2, these theories of justice are then applied to modern urban situations such as gentrification, urban segregation and affordability. This textbook will be an important resource for undergraduates and postgraduates studying human geography, urban and municipal planning, urban theory and urban politics, sociology, and politics and government"--
Introduction: Justice Theory for the Urbanist -- Utilitarianism -- Libertarianism -- Liberalism -- Marxism -- Communitarianism -- Conservativism -- Post Critiques -- Gentrification -- Urban Segregation -- Housing Affordability -- Conclusions (via Camus).
Keywords: Urbanization -- Moral and ethical aspects; Sociology, Urban; Social justice; Equality; POLITICAL SCIENCE / Public Policy / City Planning & Urban Development; SCIENCE / Earth Sciences / Geography; SOCIAL SCIENCE / Human Geography